Interaction between CIEDs and modern radiotherapy techniques: Flattening filter free-VMAT, dose-rate effects, scatter radiation, and neutron-generating energies. (November 2020) - Gauter-Fleckenstein, Benjamin; Nguyen, Julia; Jahnke, Lennart; Gaiser, Timo; Rudic, Boris; Büttner, Sylvia; Wenz, Frederik; Borggrefe, Martin; Tülümen, Erol
Highlights: ICDs investigated with 6 and 10 MV FFF-VMAT. 6 MV FFF-VMAT is safely applicable with ICDs in 2.5 cm or 35 cm distance. 10 MV FFF-VMAT already causes ICD-failures. High dose-rates may be applied in the vicinity of ICDs. Abstract: Background and purpose: Providing evidence for radiotherapy (RT)-induced effects on cardiac implantable electric devices (CIEDs) with focus on flattening filter free-volumetric modulated arc therapy (FFF-VMAT) at 6 and 10 MV as well as 3D-conformal radiotherapy (3D-CRT) at 18 MV. Materials and methods: 68 CIEDs (64 implantable cardioverter-defibrillators (ICDs) and 4 cardiac pacemakers (PMs)) were located on the left chest position on a slab phantom and irradiated under telemetrical surveillance either directly, or distant to 3D-CRT or FFF-VMAT, dose-rate 2500 cGy/min, and target dose of 150 Gy. Devices were placed within, close by (2.5 cm and 5 cm), and distant (35 cm) to the radiation field. Scatter radiation (SR) and photon neutrons (PN) were recorded. CIEDs were investigated in following groups: 1a) 18 MV 3D-CRT − 4 ICDs/4 PMs out of radiation field, 1b) 18 MV open field − 4 ICDs/4 PMs within radiation field, 2) 6 MV FFF-VMAT, 15 ICDs in 35 cm distance to VMAT, 3) 10 MV-FFF VMAT, 15 ICDs in 35 cm distance to VMAT, 4) 6 MV FFF-VMAT, 15 ICDs in 2.5 cm distance to VMAT, 5) 10 MV FFF-VMAT, 15 ICDs in 2.5 cm distance to VMAT. Results: No incidents occurred at 6 MV FFF. 10 MV FFF-VMAT and 18 MV 3D-CRT resulted in data loss, reset, and erroneous sensing with inhibition of pacing (leading to inadequate defibrillation) in 8/34 ICDs and 2/4 PMs which were not located within radiation. Direct radiation triggered instantaneous defibrillation in 3/4 ICDs. Conclusions: 6 MV FFF-VMAT is safe even at high dose-rates of 2500 cGy/min, regardless whether CIEDs are located close (2.5 cm) or distant (35 cm) to the radiation beam. CIEDs should never be placed within radiation and energy should always be limited to 6 MV. At 6 MV, VMAT at high dose-rates can be used to treat tumors, which are located close to CIEDs.